Laser Speckle Imaging of Rat Pial Microvasculature during Hypoperfusion-Reperfusion Damage - Mastantuono, Teresa; Starita, Noemy; Battiloro, Laura; Di Maro, Martina; Chiurazzi, Martina; Nasti, Gilda; Muscariello, Espedita; Cesarelli, Mario; Iuppariello, Luigi; D’Addio, Gianni; Gorbach, Alexander; Colantuoni, Antonio; et al. (Frontiers in Cellular Neuroscience, 2017)
The present study was aimed to in vivo assess the blood flow oscillatory patterns in rat pial microvessels during 30 min bilateral common carotid artery occlusion (BCCAO) and 60 min reperfusion by laser speckle imaging. Pial microcirculation was visualized by fluorescence microscopy. The blood flow oscillations of single microvessels were recorded by laser speckle imaging; spectral analysis was performed by Wavelet transform. Under baseline conditions, arterioles and venules were characterized by blood flow oscillations in the frequency ranges 0.005-0.0095 Hz, 0.0095-0.021 Hz, 0.021-0.052 Hz, 0.052-0.150 Hz and 0.150-0.500 Hz. Arterioles showed oscillations with the highest spectral density when compared with venules. Moreover, the frequency components in the ranges 0.052-0.150 Hz and 0.150-0.500 were predominant in the arteriolar total power spectrum; while, the frequency component in the range 0.150-0.500 Hz showed the highest spectral density in venules. After 30 min BCCAO, the arteriolar spectral density decreased compared to baseline; moreover, the arteriolar frequency component in the range 0.052-0.150 Hz significantly decreased in percent spectral density, while the frequency component in the range 0.150-0.500 Hz significantly increased in percent spectral density. However, an increase in arteriolar spectral density was detected at 60 min reperfusion compared to BCCAO values; consequently, an increase in percent spectral density of the frequency component in the range 0.052-0.150 Hz was observed, while the percent spectral density of the frequency component in the range 0.150-0.500 Hz significantly decreased. The remaining frequency components did not significantly change during hypoperfusion and reperfusion. The changes in blood flow during hypoperfusion/reperfusion caused tissue damage in the cortex and striatum of all animals. In conclusion, our data demonstrate that the frequency component in the range 0.052-0.150 Hz, related to myogenic activity, was significantly impaired by hypoperfusion and reperfusion, affecting cerebral blood flow distribution and causing tissue damage.